MORPHOLOGICAL CHANGES IN THE TUBULES OF THE NEPHRON IN THE LATE STAGES OF CHRONIC OPIOID INFLUENCES - Vilhova, I.V. (World of Medicine and Biology, 2018)
The work is a fragment of the Department of Normal Anatomy of the Danylo Halytsky Lviv National Medical University "Structural organization, angioarchitectonics and anthropometric peculiarities of organs in the internal and extrabranch periods of development, under conditions of exo - and endogenous factors" (state registration number 0115U000041). Investigation of the structures of the components of the nephron in the long-term use of narcotic analgesics at different times is an urgent area of morphological research. This is due to the urgency of the problems of drug addiction in both social and medical aspects. The purpose of the study is to study the changes of proximal vorticular tubules, loops of the nephron, distal vorticular tubules with prolonged use of nalbuphina in the late terms of the experiment. The purpose of the study is to study the changes of proximal vorticular tubules, loops of the nephron, distal convoluted tubules with prolonged use of nalbuphina in the late terms of the experiment. Materials and methods of research. The research material was used by 32 sexually mature female male rats "Vistar" with an initial weight of 160-170 g, age 4.5-5.5 months. Animals were injected with nalbuphina for 98 days. Narcotic analgesics were administered to experimental animals at increasing doses. The material was collected in eight, ten, twelve and fourteen weeks. Histologic preparations were prepared according to the generally accepted method. As a result of the study, it was found that epitheliocytes of many proximal convoluted tubules are swollen, contain eosinophilic grains, lose bristle rim. In some proximal vorticular tubules there are marked necrotic changes in the epithelium. The canals are filled with eosinophilic protein cylinders containing desquamated epithelial cells, and individual tubules are completely filled with necrotic epithelial cells. At the end of the eighth week epithelial cells of the nephron hernia, which undergo destructive changes, are sometimes found. However, in the subsequent terms of the experiment, changes in the epithelial cells of the nephron hinges are not detected. Epithelial cells of the individual distal convoluted tubules undergo necrotic changes at late delivery of naphtha. Fourteen weeks of the experiment revealed hyaline cylinders in the lumen of the distal convoluted tubules. Thus, as a result of the study, it was found that, with long-term introduction of opioids, changes in all parts of the tubules of the nephron are observed in the late stages. The most pronounced changes were detected in proximal vorticular tubules. During the experiment, in the part of the proximal convoluted tubules, signs of granular and hyaline-droplet dystrophy were revealed in late terms of opioid influence, and expressed necrotic changes. The indicated changes progress during the experiment. Epithelial cells of the neuron loops at the end of the eighth week of the experiment undergo destructive changes that are no longer observed after ten weeks of the experiment. At the end of the eighth week of the experiment and before its completion, necrotic changes in the epithelial cells of the individual distal convoluted tubules were revealed. Prospects for further research: established data on changes in the structure of the tubular channels of the nephron, which arise with prolonged administration of nalbuphina, can serve as a morphological basis for the diagnosis of nephropathy arising from the prolonged use of narcotic analgesics. The data of the conducted research can be used for the comparative characterization of tubal changes at early and late terms of long-term influence of opioids